HEREDITARY SUBSTITUTION IN CONTEMPORARY LEGAL SYSTEMS IN EUROPE - Vidić Trninić, Jelena Đ; Kovačević, Milica S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: The authors’ attention is focused on the legal regulation of hereditary substitution, that is, the replacement of inheritors as a modality of testamentary inheritance in the contemporary legal systems of Europe. The legislation in Serbia only accepts the possibility of alternative acquisition of inheritance rights, that is, vulgar substitution as a form of hereditary substitution, as well as those modalities of successive inheritance related to the fulfillment of conditions or expiry of the term, with the explicit prohibition of fideicommissary substitution in the case of death of the previous inheritor. By analyzing the domestic legislation, its advantages and some of its disadvantages, and especially considering the legal solutions to the institute of hereditary substitution in comparative law, the authors are taking the opportunity to point out the justification and possible ways of improving the existing normative concept of this institute in Serbian law. Key words: ordinary substitution, fideicommissary substitution, institute, substitute, previous (preceding) heir, subsequent (latter) heir.